2014
DOI: 10.1371/journal.pone.0098375
|View full text |Cite
|
Sign up to set email alerts
|

New Mitochondrial and Nuclear Evidences Support Recent Demographic Expansion and an Atypical Phylogeographic Pattern in the Spittlebug Philaenus spumarius (Hemiptera, Aphrophoridae)

Abstract: Philaenus spumarius is a widespread insect species in the Holarctic region. Here, by focusing on the mtDNA gene COI but also using the COII and Cyt b genes and the nuclear gene EF-1α, we tried to explain how and when its current biogeographic pattern evolved by providing time estimates of the main demographic and evolutionary events and investigating its colonization patterns in and out of Eurasia. Evidence of recent divergence and expansion events at less than 0.5 Ma ago indicate that climate fluctuations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 54 publications
9
68
0
Order By: Relevance
“…According to the results of this study and previous phylogenetic and phylogeographic works on this species (Maryańska-Nadachowska et al, 2010Seabra et al, 2010;Rodrigues et al, 2014), we can conclude that southwestern Asia is probably the place of origin of the Philaenus spumarius, or at least the main refugium for P. spumarius during the Pleistocene glaciations, from where this species spread across almost the whole Holarctic. Yet the history of this species is probably more complex, as several highly distinct subclades (known from the western and eastern Mediterranean, Crimea, the Caucasus, and Eastern Asia) need a long period of time to gain such divergence.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…According to the results of this study and previous phylogenetic and phylogeographic works on this species (Maryańska-Nadachowska et al, 2010Seabra et al, 2010;Rodrigues et al, 2014), we can conclude that southwestern Asia is probably the place of origin of the Philaenus spumarius, or at least the main refugium for P. spumarius during the Pleistocene glaciations, from where this species spread across almost the whole Holarctic. Yet the history of this species is probably more complex, as several highly distinct subclades (known from the western and eastern Mediterranean, Crimea, the Caucasus, and Eastern Asia) need a long period of time to gain such divergence.…”
Section: Discussionsupporting
confidence: 75%
“…We also found a single population in northeastern Turkey with a haplotype closest to the NE clade, however forming a substantially highly distinct phylogenetic entity. It is important to highlight that previous studies (Maryańska-Nadachowska et al, 2012;Rodrigues et al, 2014) also identified highly distinct mitochondrial clades in the Caucasus (Georgia), Crimea, and Northern Anatolia (thus, around the Black Sea). However, in all of these regions were found phylogenetic lineages different from those found in this study in Turkey and Iran.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is the most investigated species of its genus and has high genetic and morphological variation [29]. Sixteen adult colour phenotypes are known to occur in natural populations [30] but only 13 are referred in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…2006; Rodrigues et al. 2014). They also suggest that the key to understanding the origin of the R. grassei / R. banyulensis complex may lie in North African populations.…”
Section: Discussionmentioning
confidence: 99%